The Role of Job Satisfaction in Mediating The Influence of Emotional Intelligence and Leadership on Employee Performance - Sakyamuni, Ni Wayan Sri Chandra (Universitas Warmadewa, 2023)
The purpose of this study is to create and assess the role of job satisfaction in mediating the influence of emotional intelligence and leadership on employee performance. This study employed a questionnaire approach that was carried out in line with the study's goals. Warmadewa College was the topic of this study, which had 45 participants. A likert scale was employed in this study to examine factors in testing validity and reliability. As an analytical technique, PLS-based SEM was employed in the investigation. The results of this study revealed that emotional intelligence has a negative and small impact on work satisfaction. Emotional intelligence has a strong and beneficial impact on performance. Leadership has a strong and beneficial impact on job satisfaction. Leadership has a strong and beneficial impact on performance. Job happiness has a strong and favorable impact on performance. Job happiness does not operate as a buffer between emotional intelligence and performance. Job happiness does not operate as a buffer between leadership and performance.